Perancangan Prototipe Pembangkit Listrik Tenaga Surya Menggunakan Sistem Turbin Uap Dengan Fluida Kerja Refrigerant-134A - Anam, Fadhil; Wijaya Kusuma, I Gusti Bagus; Adnyana, I Wayan Bandem (Teknik Desain Mekanika, 2025)
Abstract Sunlight produces energy through its light, with one form of energy that can be utilized is heat energy. This research evaluates the use of heat energy from solar radiation which will be converted into electrical energy through a prototype. This prototype consists of several main components, which work sequentially: solar collector, heat exchanger, and steam turbine. The function of the solar collector is to capture solar radiation energy to heat the air fluid inside, which is then directed to the heat exchanger. A heat exchanger in the form of a concentric pipe will transfer heat from the air fluid to the refrigerant-134A working fluid. The refrigerant-134A working fluid which turns into steam will flow to the steam turbine and drive the turbine which is connected to the dynamo generator, so that when the turbine operates, electrical energy is produced. In theoretical ideal conditions, the prototype solar power plant with a steam turbine system receives input energy of 2245,909 W and produces an energy output of 751,904 W. Meanwhile, in non-ideal conditions, the simulation results show an energy input of 2225,004 W with an energy output amounting to 523,711 W. The system efficiency in ideal conditions is 33%, while in non-ideal conditions it is 24%. Keywords: Prototype, Design, Radiation Energy, Solar Collector, Heat Exchanger, Refrigerant-134A, Steam Turbine, Electrical Energy